Usability and evaluation of a library mobile web site. Issue 4 (1st August 2016) - ChanLin, Lih-Juan; Hung, Wei-Hsiang
Abstract : Purpose: The purpose of this study is to develop and evaluate the use of a library mobile website at a university library. This paper aims to present the approach adopted to investigate users' reactions to the new mobile platform. A usability test was also conducted to examine its effectiveness. Design/methodology/approach: Mobile websites for academic libraries were first reviewed prior to identifying the functions and elements to be included. To assess the intended design purpose, the usability of the design was examined through a comparison of the mobile website and the full PC website used by 50 students to accomplish a set of search tasks. A questionnaire survey was used to assess 336 students' responses regarding various criteria including learnability, control, presentation and efficiency. Findings: The usability test that was conducted before the mobile Web was formally released indicated that the students using it finished more search tasks ( p < 0.001), and were more efficient in completing search tasks than they were using the PC website ( p < 0.001). Data from 336 questionnaire responses also indicated the students' positive reactions to the developed mobile system in four defined facets (mean >= 4.0). Research limitations/implications: The difficulty of recruiting volunteers and the small number of subjects who participated was also a major limitation experienced in this study. Replications or use of different measurements might be needed in future research to confirm the result. Practical implications: In this study, a library mobile website was developed, tested and evaluated by users. Currently, the library mobile website is being implemented in the university. On-going revisions will continue to improve its effectiveness and efficiency for information retrieval. Social implications: It is expected that through the library mobile services, a ubiquitous learning environment can be provided to students to fulfil their academic and leisure needs. Originality/value: Summative evaluation of the mobile system revealed the students' positive reactions to a set of predetermined criteria in various dimensions, including: learnability, control, presentation and efficiency.